Human Machine Interaction Getting Closer - Inaki, Maurtua (IntechOpen, 2012)
In this book, the reader will find a set of papers divided into two sections. The first section presents different proposals focused on the human-machine interaction development process. The second section is devoted to different aspects of interaction, with a special emphasis on the physical interaction.